Primum non nocere : riflessione morale sulla relazione tra medicina ed etica - Sciagura, Tania (Sapientia, 2019)
Many bioethical questions arise in everyday clinical reality and therefore have a strongly practical profile: how can MORALS, ETHICS and MEDICINE be combined and merged? Where does the theme of this triangle come from? Starting from an introduction to the medical field and on the contribution of clinical ethics, I will proceed to analyze purposes, functions and practicality, highlighting how ancient this triage movement is, also determined by significantly social dynamics with respect to moral choices and decisions. On health and illness on an individual, interpersonal and social level. The principles and values are spreading like wildfire in the single realities and in the different practical situations with the common aim of promoting health and directing attention to those who will be able to receive care through appropriate communication and information methods.